ANALYSIS OF MnO2 RECOVERY STUDY FROM DRYCELL BATTERY WASTE: A REVIEW - Erwan Adi Saputro; Muhandis Akbar Winaji; Muchammad Fahrizal Hanif; Ardika Nurmawati; Ely Kurniati; Caecilia Pujiastuti (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
Global demand for manganese dioxide (MnO₂) materials is increasing rapidly as the battery and catalyst industry develops, while the availability of primary ores continues to decline. Waste dry cell batteries contain high amounts of MnO₂, making them potentially a secondary source of economically valuable manganese metals. This study systematically discusses various microwave-assisted hydrometallurgy-based hydrometallurgy approaches for the recovery of MnO₂ from waste batteries. The literature study was conducted by examining 50 current scientific references covering three main aspects: extraction methods, the influence of heating methods, and purification strategies. The core conclusion of this review is that microwave-assisted leaching represents the most efficient extraction approach, delivering recovery rates up to 95.1% that significantly surpassing conventional methods (82–85%) while reducing reaction times and energy consumption by up to 40%. Furthermore, this study concludes that chemical oxidation using KMnO4​ is the superior purification strategy, capable of producing MnO2​ with purity exceeding 98%. Consequently, this review establishes that the integrated system of microwave-assisted leaching and selective KMnO4​ oxidation offers the most robust, economical, and environmentally friendly blueprint for implementing a circular economy in the metals industry